The development of a lead-free replacement for the Lindlar catalyst for alkyne semi-hydrogenation using silica supported, N-doped carbon modified cobalt nanoparticles. Issue 18 (23rd August 2022) - McNeice, Peter; Müller, Marc-André; Medlock, Jonathan; Bonrath, Werner; Rockstroh, Nils; Bartling, Stephan; Lund, Henrik; Junge, Kathrin; Beller, Matthias
Abstract : The synthesis of vitamin precursors via alkyne semi-hydrogenation has been achieved with a lead- and palladium-free catalyst. Abstract : The synthesis of vitamin precursors via alkyne semi-hydrogenation has been achieved with a lead- and palladium-free catalyst. Cobalt nanoparticles modified by nitrogen doped carbon and supported on silica allow the production of a range of fine chemicals and vitamin precursors. The optimal catalyst could be conveniently recycled and used for at least five runs with consistent activity. Interestingly, this material selectively hydrogenates alkynes in the presence of easily reducible, cyano-, keto-, aldehyde-, and even nitro groups, which shows it to be a versatile catalyst for synthetic organic chemistry.